Mengembangkan Aktivitas, Kerjasama, Dan Kognitif Dalam Mengenal Konsep Dan Lambang Bilangan Menggunakan Model PBL Dan MAM - Maulidatun Noor Syifa; Aslamiah Aslamiah (CV. ITTC INDONESIA, 2025)
The problem in this study is the low level of children's activity, cooperation, and cognitive aspects in recognizing number concepts and symbols. The cause of the problem occurs due to the use of learning models that are less innovative and creative, and the lack of children's participation during learning. The solution is to use a combination of Problem Based Learning and Make A Match Models with interesting teaching materials. The purpose of this study is to describe teacher activities, analyze the increase in activity, cooperation, cognitive aspects in recognizing number concepts and symbols. The type of classroom action research was carried out in 4 meetings. The subjects of the study were 16 children in Group A at the Baitul Makmur Islamic Integrated Preschool, Banjarmasin. The results showed that teacher activity reached very good criteria, children's activity reached 100% of the criteria for all active children, cooperation reached 100% of the criteria for all active children, and cognitive development reached 100% of the BSB criteria. It is recommended to use this model as an alternative for developing children's cognitive aspects in recognizing number concepts and symbols.